A comunicação pública como política e aliada estratégica nas políticas públicas para a segurança pública: Pronasci/Protejo - Nascimento, Rosangela Eugenia Gonçalves (2013)
This research has a structural cutout dealing with public communication for public policies of the public safety program Pronasci/Protejo a Youth Protection Project in Vulnerable Territory of the Justice Department. Thus, this work will be divided into three chapters: the two first reflections and criticisms has been made about of both public safety and communications. In the last chapter there are reflections, sometimes analytical and sometimes critical, and maps of the historical and lawful contexts that contributed between the public communication and the public safety and points the public communications as one of the ways to achieve public policies objectives